Impact of COVID-19 on Orthopaedic Surgery: Comparison Between Before and During COVID-19 Pandemic - Bhandari, Ravi; Magar, Mohit Thapa; Shrestha, Sushil; Sinha, Ritesh; Kayastha, Nirab; Thapa, Bishnu Babu (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Orthopaedic surgical activity has been significantly affected by COVID-19 pandemic. The decision to perform operative interventions is based on balancing risk to benefit to the patient and health care workers. Though different guidelines have been published, there is a lack of reliable data on orthopaedic surgical activities. Our study aimed to evaluate the impact of the COVID-19 pandemic on Orthopaedic surgeries comparing with the previous year. Methods: This was an epidemiological retrospective comparative study conducted at Shree Birendra Hospital, Nepal after taking ethical approval from the Institutional Review Committee of NAIHS. Data of the first four month of orthopaedic surgeries after National lockdown (from March 24 to July 23, 2020) and the same four month period of the previous year (The year 2019) were retrieved. The demographic profiles and operations categories (trauma, elective and infections) were compared between two periods using SPSS 21. Result: Out of total of 651 patients enrolled, 169 patients operated during the pandemic compared with 482 patients before the pandemic. There was a 65% reduction in total surgical procedures, 94% reduction in elective cases and trauma cases were reduced by 29% (P < 0.05). Implant removal (107, 42.8%) constituted the highest elective cases in the year 2019. Conclusions: The orthopaedic surgical procedures were decreased in frequency during COVID-19 because of a decrease in elective cases. The total trauma patients remained more equable during pandemic despite strict lock-down. Health care facilities should consider this during post pandemic recovery.